2020
DOI: 10.1186/s12955-020-01480-3
|View full text |Cite
|
Sign up to set email alerts
|

Electronic reporting of patient-reported outcomes in a fragile and comorbid population during cancer therapy – a feasibility study

Abstract: Background: Electronic collection of patient-reported outcomes (ePROs) is becoming widespread in health care, but the implementation into routine cancer care during therapy remains to be seen. Especially, little is known of the use and success of electronic reporting during active cancer treatment in fragile and comorbid patients. The aim of this study was to test the feasibility of ePRO and its incorporation into routine cancer care, measured by physician compliance, for a fragile and comorbid bladder cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…While only a few of our patients directly mentioned a decline in motivation to complete ePROMs due to HCPs not picking up on the results during the consultations, this is in fact a frequent problem of PRO implementations in clinical settings [ 3 , 26 , 28 , 29 ]. For patients, there is little perceived benefit of completing the questionnaires if the results are not reviewed and discussed by HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…While only a few of our patients directly mentioned a decline in motivation to complete ePROMs due to HCPs not picking up on the results during the consultations, this is in fact a frequent problem of PRO implementations in clinical settings [ 3 , 26 , 28 , 29 ]. For patients, there is little perceived benefit of completing the questionnaires if the results are not reviewed and discussed by HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…The overall completeness of data was 93% (7% missing values). See a detailed description of the adherence data in a separate publication [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…), if needed. Further details regarding these procedures can be reviewed in a separate publication [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The specific scores from the EORTC and HADS questionnaires are hence the aim of this study reported elsewhere …”
Section: Methodsmentioning
confidence: 99%